COMMUNICATION VOICE ASIAN OF TEACHERS - Gunadi, YS (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
The Brotherhood of Asian Trade Unions (BA TU) invites me to participate in the Congress of the Asian Confederation of Teachers (ACT) that will be conducted from 25-30 December 2007 at the YMCA International Hotel, Chiang Ma; Thailand Â By the Â congress, explaned about teachers honor at Provencial of Banten for the examples. In the same time, by aclamation, YS. Gunadi from FESDIKARI o f lndonesia has be chosen as Vice President Asian Confederation of Teachers,2007-2012 periode.